Tribological response of polycarbonate and acrylonitrile butadiene styrene blends containing fixed amounts of Kevlar fibre and molybdenum disulphide with varying quantities of betel nut powder. Issue 9 (November 2021) - Pramod, T; Sampathkumaran, P; Puneeth, N; Sailaja, RRN; Seetharamu, S; Swamy, A Sathyanarayana; Kishore,
In this study, the composites with incorporation betel nut powder at three levels (10, 18 and 25%) in Polycarbonate (PC) and Acrylonitrile Butadiene Styrene (ABS) matrices having Kevlar Fibres (KF) and Molybdenum Disulphide (MoS2 ) nano particles in fixed amounts are looked into for their tribological characteristics. The effect of hardness, surface roughness and density was evaluated. FTIR and X-ray diffraction (XRD) studies have been carried out to identify the phases. The effects of load on the slide wear loss and coefficient of friction of the composites were determined using Pin on Disc set up. The wear test pertaining to the betel nut bearing (BNP) composites were compared with those of betel nut free ones i.e. PC/ABS/KF/MoS2 . The results revealed that with increase in load, the wear loss increases. Further with increase in betel nut powder concentration from 10% to 25% there is a decrease in wear loss as well as coefficient of friction. The surface morphology of the worn surface were examined using Scanning Electron Microscopy (SEM) which revealed higher plastic deformation, debris formation and furrowing in BNP free systems compared to betel nut bearing ones.